Impact of prospective measurement of outflow tracts in prediction of coarctation of the aorta. (1st December 2020) - Vigneswaran, T. V.; Zidere, V.; Chivers, S.; Charakida, M.; Akolekar, R.; Simpson, J. M.
ABSTRACT: Objectives: Prenatal diagnosis of coarctation of the aorta (CoA) is associated with reduced mortality and morbidity, however, accurate prenatal prediction remains challenging. To date, studies have used retrospective measurements of the outflow tracts to evaluate their potential to predict CoA. Our primary objective was to evaluate prospectively acquired measurements of the outflow tracts in fetuses with prenatally suspected CoA. A secondary aim was to report the postnatal prevalence of bicuspid aortic valve in this cohort. Methods: Pregnancies with suspicion of isolated CoA and with a minimum of 6 months' postnatal follow‐up available were identified from the cardiac database of a tertiary fetal cardiology center in the UK, between January 2002 and December 2017. Measurement of the aortic valve, pulmonary valve, distal transverse aortic arch (DTAA) and arterial duct (AD) diameters were undertaken routinely in fetuses with suspected CoA during the study period. Z ‐scores were computed using published reference ranges based on > 7000 fetuses from our own unit. Results: Of 149 pregnancies with prenatally suspected CoA included in the study, CoA was confirmed within 6 months after birth in 77/149 (51.7%) cases. DTAA diameter Z ‐score and the Z ‐score of second‐trimester DTAA/AD diameter ratio were smaller in fetuses with postnatally confirmed CoA than those in false‐positive cases (–2.8 vs –1.9; P  = 0.039 and –3.13 vs –2.61; P  = 0.005, respectively). Multiple regression analysis demonstrated that the Z ‐scores of DTAA and AD diameters were the only significant predictors of postnatal CoA ( P  = 0.001). Bicuspid aortic valve was identified in 30% of the false‐positive cases. Conclusions: Measurement of DTAA and AD diameter Z ‐scores can be used to ascertain risk for postnatal CoA in a selected cohort. The high incidence of bicuspid aortic valve in false‐positive cases merits further study with respect to both etiology and longer‐term significance. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.